Management of musculoskeletal pain in a compensable environment: Implementation of helpful and unhelpful Models of Care in supporting recovery and return to work - Beales, Darren; Fried, K.; Nicholas, M.; Blyth, F.; Finniss, D.; Moseley, G. (Bailliere Tindall, 2016)
© 2016 Elsevier LtdModels of Care (MoCs) for injured workers in the compensation environment recommend adoption of biopsychosocial management approaches. Still, widespread dominance of biomedical constructs at the system, organisational and individual levels of the compensation system prevails, contributing to suboptimal management practices and outcomes for injured workers. Efforts to implement contemporary MoCs in the compensation environment show some promise in improving outcomes. Areas of promise at the organisational level, particularly in the workplace, and at the system level are discussed. Implementation of a contemporary understanding of pain biology as part of the biopsychosocial approach in the management of the person with pain and associated disability has been effective in the non-compensable environment. The implications of this for the compensable environment are explored. Resultant helpful and unhelpful perspectives and behaviours are presented as a blueprint for areas of potential change in development and implementation of MoCs in a compensable environment.